Nuevas localidades para peces de agua dulce de la República Argentina, I - López, Hugo Luis (1980)
Four species of Characiformes (Astyanax eigenmanniorum, Characidium rachowi, Curimatopsis saladensis and Pseudocurimata nitens) and five species of Siluriformes (Hypophthalmus edentatus, Megalodoras laevigatulus, Homodiaetus maculatus, Cataphractos melampterus and Hoplosternum thoracatum thoracatum) are recorded from ten new Argentine localities. New distributional data are discussed. Relevant morphological measurements and some comments are added.